2007
DOI: 10.1016/j.bbr.2007.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Selective hippocampal cholinergic deafferentation impairs self-movement cue use during a food hoarding task

Abstract: Investigations using selective lesion techniques suggest that the septohippocampal cholinergic system may not be critical for spatial orientation. These studies employ spatial tasks that provide the animal with access to both environmental and self-movement cues; therefore, intact performance may reflect spared spatial orientation or compensatory mechanisms associated with one class of spatial cues. The present study investigated the contribution of the septohippocampal cholinergic system to spatial behavior b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 69 publications
1
24
1
Order By: Relevance
“…For example, separate representations of direction and distance appear to converge on the hippocampus [49]. Accordingly, damage to the hippocampal formation [53, 54] or selective hippocampal deafferentation [55, 56] has been suggested to impair self-movement cue processing while sparing the use of environmental cues. The sequential analysis of exploratory behavior provides an alternative assessment of spatial orientation that is more acute and does not depend on food deprivation or other motivational factors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, separate representations of direction and distance appear to converge on the hippocampus [49]. Accordingly, damage to the hippocampal formation [53, 54] or selective hippocampal deafferentation [55, 56] has been suggested to impair self-movement cue processing while sparing the use of environmental cues. The sequential analysis of exploratory behavior provides an alternative assessment of spatial orientation that is more acute and does not depend on food deprivation or other motivational factors.…”
Section: Discussionmentioning
confidence: 99%
“…Rats use environmental (i.e., visual, auditory, olfactory) and internally generated or self-movement (i.e., vestibular, proprioceptive, efferent copies of motor commands) cues to maintain spatial orientation. Immunotoxic lesions of the medial septum have been shown to spare performance on tasks in which rats can use environmental cues to guide navigation (Baxter, Gallagher 1996; McMahan et al, 1997; Cahill and Baxter, 2001; Frielingsdorf et al, 2006); whereas, impaired performance has been observed on tasks in which rats were restricted to using trial unique self-movement cues to guide navigation (Martin, Wallace, 2007). These results are consistent with a growing literature positing a role for the hippocampal formation in the online processing of self-movement cues to maintain spatial orientation (Maaswinkel et al, 1999; Wallace, Whishaw, 2003; Martin et al, 2007; for a review see Wallace et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, dead reckoning based navigation depends on processing self-movement cues in the appropriate temporal context to estimate the direction and distance to the point where movement was initiated (Barlow, 1964; Mittelstaedt, Mittelstaedt, 1980; Etienne, 1980; Gallistel, 1990; Etienne and Jeffery, 2004; Wallace et al, 2008). Interestingly, a growing number of studies have demonstrated a role for the septohippocampal system in dead reckoning based navigation (Maaswinkel et al, 1999; Wallace, Whishaw, 2003; Martin et al, 2007; Martin, Wallace, 2007). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations